A process-philosophical understanding of organizational learning as "wayfinding": Process, practices and sensitivity to environmental affordances. Issue 2 (6th February 2017) - Chia, Robert
Abstract : Purpose: This paper aims to articulate a practice-based, non-cognitivist approach to organizational learning. Design/methodology/approach: This paper explores the potential contribution of a process-based "practice turn" in social theory for understanding organizational learning. Findings: In complex, turbulent environments, robust organizations recur more to cultivated sensitivities and predispositions rather than rely on elaborate plans and strategies to guide their action; they "Wayfind" their way to sustainable success. Originality/value: This study develops the understanding of organizational learning as a process of everyday practical coping guided by internalized sensitivities and predispositions.